PENGGUNAAN APLIKASI QUIZIZZ SEBAGAI ALAT EVALUASI PEMBELAJARAN DALAM HUKUM NEWTON TENTANG GERAK - Munjaidah; Jimmy Lolowang; Farly Tumimomor (Charm Sains: Jurnal Pendidikan Fisika, 2021)
For better education it is necessary to use information and communication technologies to support the learning process and tools for quality assessment. The Quizizz application is an online based learning assessment tool that can be used by teachers and students. Newton's law of motion was examined using the Quizizz application learning assessment tool. The purpose of this study was to determine whether the Quizizz evaluation tool was effective in improving students' learning outcomes using Newton's law of motion. This study was carried out on class X students of the SMA Negeri 1 Tondano with 21 respondents who use the Quizizz application as a learning assessment tool. The design of this study used the One Group Pretest-Posttest design and the tools used were Pretest and Posttest using the Quizizz application learning assessment tool. This research begins with the pretest, the implementation of the physics learning with Zoom Meeting and ends with the post-test. The results of this study gave an average score of 29.90 pretest and posttest scores of 85.10. The results of the N-Gain test give a value of 79.0985, as can be seen from the categorization of the effectiveness interpretation with a percentage> 76%. So it can be said that learning Newton's law of motion with the Quizizz learning assessment tool falls into the effective category.